Diverse Dust Populations in the Near-Sun Environment Characterized by PSP/ISʘIS - M. M. Shen; J. R. Szalay; P. Pokorný; J. G. Mitchell; M. E. Hill; D. G. Mitchell; D. J. McComas; E. R. Christian; C. M. S. Cohen; N. A. Schwadron; S. D. Bale; D. M. Malaspina (The Astrophysical Journal)
The Integrated Science Investigation of the Sun energetic particle instrument suite on the Parker Solar Probe is dedicated to measuring energetic ions and electrons in the near-Sun environment. It includes a half-sky-viewing time-of-flight mass spectrometer (EPI-Lo) and five high-energy silicon solid-state detector-telescopes (EPI-Hi). To 2024 August, eight of EPI-Lo’s eighty separate telescope foils have experienced direct dust puncture events, most of which occurred inside 40 solar radii (0.19 au). These impacts represent the closest high-fidelity dust detections to the Sun. While there is limited information about the size/mass of each impact due to the lack of a dedicated dust instrument, we can determine the impact direction for six punctures, allowing us to partially constrain abundant dust populations in the inner zodiacal cloud. Remarkably, one of six unambiguous dust impactors was likely on a retrograde orbit, suggesting long-period cometary material may survive within 20 solar radii (0.09 au). We discuss observations in the context of highlighting multiple dust populations responsible for these events to improve our understanding of the zodiacal dust environment in the inner heliosphere ( $\lesssim $ 1 au).